Hubungan Kecanduan Game Online dengan Keterampilan Sosial Siswa - Saputra, Indro; Firman, Firman (Lembaga Yasin AlSys, 2024)
This research is motivated by the low social skills of students caused by online game addiction. Ideally, the lower the addiction to online games in students who use online games, the higher the social skills. However, it can still be found that students experience online game addiction, which affects their social skills in interacting with others. This study aims to determine the relationship between online game addiction and the social skills of students who use online games. This research uses quantitative methods with correlational research types. The sample in this study was 65 students selected using purposive sampling technique. The data were processed using descriptive analysis techniques and Pearson product moment correlation analysis. The results showed that students' online game addiction was in the high category with a percentage (38.5%), the social skills of online game users were in the low category with a percentage (35.4%) and there was a significant and negative relationship between online game addiction and social skills in online game users with a correlation value of r count of -0.348 with a significance level of <0.04 at a weak level of relationship.